Concepts, models, and methods in computational heterogeneous catalysis illustrated through CO2 conversion - Morales‐García, Ángel (2021)
Theoretical investigations and computational studies have notoriously contributed to the development of our understanding of heterogeneous catalysis during the last decades, when powerful computers have become generally available and efficient codes have been written that can make use of the new highly parallel architectures. The outcomes of these studies have shown not only a predictive character of theory but also provide inputs to experimentalists to rationalize their experimental observations and even to design new and improved catalysts. In this review, we critically describe the advances in computational heterogeneous catalysis from different viewpoints. We firstly focus on modeling because it constitutes the first key step in heterogenous catalysis where the systems involved are tremendously complex. A realistic description of the active sites needs to be accurately achieved to produce trustable results. Secondly, we review the techniques used to explore the potential energy landscape and how the information thus obtained can be used to bridge the gap between atomistic insight and macroscale experimental observations. This leads to the description of methods that can describe the kinetic aspects of catalysis, which essentially encompass microkinetic modeling and kinetic Monte Carlo simulations. The puissance of computer simulations in heterogeneous catalysis is further illustrated by choosing CO2 conversion catalyzed by different materials for most of which a comparison between computational information and experimental data is available. Finally, remaining challenges and a near future outlook of computational heterogeneous catalysis are provided.